Purification, characterization, and antibacterial and antibiofilm activity of a novel bacteriocin against Salmonella Enteritidis. (September 2021) - Xiang, Yi-Zhou; Zhang, Yan-Mei; Liu, Ying-Yang; Zhang, Man; Lin, Lian-Bing; Zhang, Qi-Lin
Abstract: Planktonic Salmonella Enteritidis and their biofilm threaten human health through the food chain. However, the resources of bacteriocins with activity against this threat are still limited. This study purified and characterized a novel bacteriocin ( AMYX6 ) produced by the Bacillus amyloliquefaciens strain JDF-17, isolated from the intestine of the Nile tilapia ( Oreochromis niloticus ). The analysis results of ÄKTA Purifier and nano liquid chromatography coupled with tandem mass spectrometry uncovered a molecular mass of 1323.73 Da and an amino acid composition of PVFLSDHIRIQ. AMYX6 inhibited the strain of S. Enteritidis CMCC(B)50335 ( S. Enteritidis_35). AMYX6 also showed good resistance to heat and acid-base treatments, and was found to be sensitive to proteases such as trypsin, protease K, papain, and pepsin. The minimum inhibitory concentration of AMYX6 against S. Enteritidis_35 was 12.17 μg/mL, which is lower than the levels reported for most bacteriocins. Furthermore, exposure to AMYX6 significantly inhibited ( p  < 0.05) planktonic S. Enteritidis_35 cells and decreased their viability. Biofilm formation of S. Enteritidis_35 was also significantly inhibited ( p  < 0.05). Electron microscopy showed that AMYX6 impaired the membrane integrity of S. Enteritidis_35, and caused leakage of cytoplasmic content and cell deformation. In summary, the novel bacteriocin AMYX6 offers good potential for the control of S. Enteritidis in either planktonic or biofilm states in food safety and control. Highlights: A novel bacteriocin designated as AMYX6 was purified and characterized. Molecular mass and amino acid composition of AMYX6 were revealed. The bacteriocin reduced viability and promoted death of planktonic S. Enteritidis cells. The biofilm formation is inhibited after bacteriocin treatment. The bacteriocin cause permeability and deformation of S. Enteritidis cells.